Faktor - faktor yang mempengaruhi produksi petani pinang di Desa Sungai Gebar Barat Kecamatan Kuala Betara - Ridho Arifullah; Yulmardi Yulmardi; Hardiani Hardiani (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2017)
This study aims to analyze: 1) socio-economic conditions of areca nut farmers; 2) factors that influence the production of areca nut farmers. The data used is sourced from surveys on areca nut farmers in the Sungai Gebar Barat Village. Data were analyzed descriptively and used multiple regression models. The results of the study found: 1) The average age of areca farmers in the Sungai Gebar Barat Village was 42 years. The average number of areca nut farmer family members is 4 people. Education level is dominated by senior secondary education; 2) The average production of areca nut farmers in the Sungai Gebar Barat Village is 256.94 kg per month. Land area and labor have a significant positive effect on areca nut production, while production costs and prices have no significant effect